«Блакитна троянда» Лесі Українки: психіатрія, біографія і сексуальність (із додатком: Леся Українка. «Крафт-Эбинг. Психиатрия». Виписки) - Гундорова, Т. (Слово і Час, 2021)
У статті досліджується «Блакитна троянда» (1896) Лесі Українки в
термінах rite de passage — як текст, що має ритуальну функцію й відображає зміну культурного й гендерного статусу авторки на полі літератури.
Ця перша п’єса авторки моделює акт ініціації в культуру fin de siècle. Особливі ознаки такого ритуалу — критичні коментарі щодо модерної культури, перетворення фактів автобіографії на естетичні феномени та інтеріоризація мотиву смерті. Образ жіночого божевілля й «ненормальної любові», критика міщанського щастя й патріархальності становлять
важливі аспекти цієї драми. Аналіз твору у світлі неопублікованих
матеріалів з архіву Лесі Українки — її нотаток із праці Р. Крафта-Ебінґа
«Психіатрія» — дає підстави зробити висновок, що у «Блакитній троянді» божевілля трактується психіатрично, а не як психологічний феномен. Важливою у драмі є дискусія щодо материнської влади й материнства
та відсилання до неоплатонізму, який пізніше асоціюватиметься в Лесі Українки з новоромантичним поривом ins Blau. The paper explores “the Blue Rose” (1896) by Lesia Ukrainka in terms of the ‘rite de passage’
as the text with a ritual function that reflects the cultural, gender, and author status
transformations within the field of literature. In the most general sense, the first drama by
Lesia Ukrainka is analyzed as an act of initiation into the fin de siècle culture. Peculiar features
of this ritual are the critical comments of the modern culture, transformation of the
autobiographical facts into aesthetic phenomena, and interiorization of the motif of death.
“the Blue Rose” discusses a female genetic illness — a popular topic of the late 19th
century — and depicts an attempt of escaping into the illusionary world of platonic love.
Representation of the female insanity and ‘unconventional love’, as well as the critique of
a bourgeois view of happiness and the patriarchal world, is also an important aspect of the
drama. References to the unpublished materials of Lesia Ukrainka’s archive — her excerpts
from the “Psychiatry” by Krafft -Ebing — allow concluding that “the Blue Rose” treats insanity
as a psychiatric and not a psychological phenomenon. the mother-daughter relations
as well as the tension of the mother-son relations in the family of Kosaches are also an important
element in Lesia Ukrainka’s work.
“the Blue Rose” (1896) is a multidimensional and experimental drama. Its author
transforms numerous autobiographical facts into cultural situations and engages in a discussion
on the topical themes and motifs of the fin de siècle, in particular female insanity,
hysteria, and maternity. the writer employs naturalistic methods of analysis and reinforces
descriptions of female insanity with the facts from psychiatric practice. “the Blue Rose”
displays an interest of Lesia Ukrainka in Neoplatonism, which she would later associate with
a Neo-romantic impulse ‘ins Blaue’.
In general, the author did not follow the foreign patterns, as the critiques noted, but
explored the Zeitgeist of the new era. She involved authentic practical experience of her
own life and the lives of her relatives and friends, analyzed moral norms and psychological
states referring to the cultural codes that ranged from “the Romance of the Rose”, Dante,
Shakespeare, and Heine to Zola, Ibsen, and Nadson. this practice ensured Lesia Ukrainka’s
initiation into the fin de siècle culture and paved her way to the modernist drama.